(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Neonatal hypoglycemia is a frequent and serious complication among preterm infants, often linked to maternal medical conditions. This study investigates the impact of maternal diabetes and hypertension on the incidence of hypoglycemia in preterm neonates. Objective: To assess the association between maternal diabetes and hypertension with the incidence of hypoglycemia in preterm neonates admitted at the Paeds Ward, Nishtar Hospital, Multan. Methods: A prospective observational study was conducted from 15 February to 15 August 2025 at Nishtar Hospital, Multan.168 preterm neonates (<37 weeks of gestation) admitted during the study period were enrolled according to the study’s inclusion criteria. Maternal history of diabetes and hypertension was recorded. Neonatal blood glucose was measured at the time of admission and during the first 24 hours after birth. Hypoglycemia was defined as blood glucose <40 mg/dL. Data were analyzed using SPSS version 27, and associations were determined using chi-square tests and odds ratios (OR) with 95% confidence intervals. Results: Among 168 preterm neonates, 38 (22.6%) developed hypoglycemia. A significant association was found between maternal diabetes and neonatal hypoglycemia (OR = 6.2; 95% CI: 2.3–16.8; p = 0.01). Similarly, maternal hypertension was significantly associated with neonatal hypoglycemia (OR = 4.1; 95% CI: 1.6–10.6; p = 0.03). Conclusion: Maternal diabetes and hypertension significantly increase the risk of hypoglycemia in preterm neonates. Enhanced monitoring protocols for high-risk neonates are recommended.